The scalable growth of high-performance nanostructured heterojunction photoanodes for applications in tandem photoelectrochemical-photovoltaic solar water splitting devices - Tam,B; Pike,SD; Nelson,J; Kafizas,A (Chemical Science, 2025)
Due to their complementary absorption characteristics and band energy structure, the BiVO4-coated WO3 heterojunction architecture is commonly employed as a metal oxide photoanode for the water oxidation half-reaction. The energy level ordering results in a staggered heterojunction that can effectively separate photoexcited electrons into the WO3 layer towards the current collector and photoexcited holes into the BiVO4 layer towards the interface with the electrolyte. Chemical vapour deposition (CVD) is an upscalable technique for fabricating large-area thin films of a wide range of semiconductors with nanoscale control. The fluorine-doped tin oxide (FTO)-coated transparent conductive glass substrates used herein are mass-produced by the glass industry with atmospheric pressure CVD and so the entire photoelectrode could be produced in one production process on float glass panels. This work is a detailed study of the use of atmospheric pressure CVD to fully-fabricate high-performance BiVO4-coated WO3 nanostructures (500–2000 nm in length with 25–100 nm thick BiVO4 coatings) for photoelectrochemical (PEC) water splitting. Incident photon-to-current efficiency measurements were used to calculate optimal solar predicted photocurrents of 1.92 and 2.61 mA cm−2 (2.3% and 3.2% solar-to-hydrogen efficiency if coupled to a hypothetical photovoltaic providing 1.23 V) for WO3/BiVO4 heterojunction samples under front and back-illumination, respectively. The heterojunction showed more than additive improvements over the parent materials, with bare WO3 and BiVO4 samples showing 0.68 and 0.27 mA cm−2 and 0.50 and 0.87 mA cm−2 under front and back-illumination, respectively. Simulations of the current–voltage characteristics of tandem crystalline silicon photovoltaic modules coupled to the PEC devices were consistent with the solar predicted photocurrents. These promising results for BiVO4-coated WO3 nanoneedles fully-deposited by atmospheric press